Old Polish Discourse on the Sacred and the Profane in the Moral-religious Guide-book, Titled “Tobias the Pious and Diligent Host” (1647) - Krzysztofik, Małgorzata (Respectus Philologicus, 2017)
The article is devoted to the interpretation of the discourse on the sacred and the profane in anonymous moral-religious guidebook titled Tobiasz pobożny i gospodarz dozorny (Tobias the Pious and Diligent Host), published in Krakow in 1647. The author analyses everyday human life and its basic aspects, continually confronting them with the Bible.This gives an excellent example of intermingling of two spheres of existence in everyday life, in Old Polish literature, i.e. the sacred and the profane. For this reason, the following research objectives are set out: to select those aspects of reality that, in the mentality of the author, belong to the realm of the sacred, and those that are specific to the area of the profane. The phenomenon of persuasive sacralisation of everyday life, the essence of which is to impart sacred aspects to non-sacred phenomena of existence are described, and the methods of entering into the relationship with the sacred, presented in the text are discussed. The author believes that the persuasion presented in Tobias the Pious, established in religious-ontological discourse, is intended for sacralisation of the profane sphere.
Keywords: sacred; profane; sacralisation; Old Polish guide; discourse